Application of Sulfonic Acid Functionalised Hybrid Silicas Obtained by Oxidative Cleavage of Tetrasulfide Bridges as Catalysts in Esterification Reactions. Issue 4 (18th February 2013) - López, María Isabel; Esquivel, Dolores; Jiménez‐Sanchidrián, César; Romero‐Salguero, Francisco José
Abstract Hybrid materials with tetrasulfide bridges were synthesised by co‐condensation between bis[3‐(triethoxysilyl)propyl]tetrasulfide and either tetraethyl orthosilicate or 1, 4‐bis(triethoxysilyl)benzene under acidic conditions in the presence of Brij‐76 as a structure‐directing agent. They were post‐modified by treatment with H2O2 for 3 h or 24 h. A progressive loss of the mesostructure in the resulting materials was observed upon increasing the S content in the synthesis mixtures. Thus, only those samples with the lowest tetrasulfide content could be considered as periodic mesoporous organosilicas. This effect was even more pronounced upon oxidation. The oxidised materials exhibited a considerable acidity, particularly those with the two precursors in approximately equal amounts. All sulfonic acid functionalised materials were used as catalysts in the esterification of acetic acid with ethanol, and they exhibited a comparable or very similar activity to that of Amberlyst‐15. Several mesoporous and microporous hybrid materials were selected and compared to this commercial resin in the transformation of more hydrophobic substrates. Some of these hybrid materials were especially attractive for the transformation of benzyl alcohol and various secondary alcohols.